1999
DOI: 10.1089/lap.1999.9.135
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Surgery Complications Associated with Trocar Tip Design: Review of Literature and Own Results

Abstract: In the last 10 years, there has not been an abdominal surgical procedure that has not been performed by laparoscopic means. The enthusiasm of surgeons active in this field often neglects problems, especially with basic instruments which are important vehicles for the laparoscopic technique. The purpose of this study was to focus on trocar-related problems with special respect to the tip design. On the basis of a prospective study of laparoscopic transperitoneal hernia repair (TAPP) and laparoscopic Nissen fund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0
9

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 25 publications
4
45
0
9
Order By: Relevance
“…There is a tenfold increase in the incidence of extraumbilical hernias, if a 12-mm port is used. Other factors incriminated include long duration of surgery and multiple insertions, large quantities of fluid left in the peritoneal cavity, inadequate evacuation of pneumoperitoneum and unrelaxed abdominal wall at the end of the procedure, and increased abdominal pressure at the end of surgery [75, 76]. …”
Section: Ih After Laparoscopic Surgerymentioning
confidence: 99%
“…There is a tenfold increase in the incidence of extraumbilical hernias, if a 12-mm port is used. Other factors incriminated include long duration of surgery and multiple insertions, large quantities of fluid left in the peritoneal cavity, inadequate evacuation of pneumoperitoneum and unrelaxed abdominal wall at the end of the procedure, and increased abdominal pressure at the end of surgery [75, 76]. …”
Section: Ih After Laparoscopic Surgerymentioning
confidence: 99%
“…Many authors have recommended the deflation of pneumo-peritonium prior to port removal so that omentum and intestines are not drawn into the fascial defect. Other techniques to prevent herniation include fascial closure using fascial closure device, suture carrier and Deschamps needle [5,6]. Some authors have also reported a lower incidence of hernias with the use a paramedian incision and non bladed trocars which have a conical tip [6].…”
Section: Discussionmentioning
confidence: 99%
“…Port site hernias may have significant morbidity as the smaller size of the defect can lead to entrapment and strangulation of bowel and omentum. The risk of a trocar site hernia is 0.8-1.2% [72]. The rate of hernia occurrence is higher with 12 mm trocars (as opposed to 10 mm or 5 mm) [73] and with cutting trocars (as opposed to blunt or radially expanding) [74].…”
Section: Perioperative Considerationsmentioning
confidence: 99%